Nano-sculptured Janus-like TiAg thin films obliquely deposited by GLAD co-sputtering for temperature sensing. (26th June 2018) - Pedrosa, Paulo; Ferreira, Armando; Martin, Nicolas; Arab Pour Yazdi, Mohammad; Billard, Alain; Lanceros-Méndez, Senentxu; Vaz, Filipe
Abstract: Inclined, zigzag and spiral TiAg films were prepared by glancing angle co-deposition, using two distinct Ti and Ag targets with a particle incident angle of 80° and Ag contents ranging from 20 to 75 at%. The effect of increasing Ag incorporation and columnar architecture change on the morphological, structural and electrical properties of the films was investigated. It is shown that inclined columnar features ( β  = 47°) with high porosity were obtained for 20 at% Ag, with the column angle sharply decreasing ( β  = 21°) for 50 at% Ag, and steeply increasing afterwards until β = 37° for the film with 75 at% Ag. The sputtered films exhibit a rather well-crystallized structure for Ag contents ≥50 at%, with a TiAg (111) preferential growth. No significant oxidation was detected in all films, except for the one with 20 at% Ag, after two 298–473–298 K temperature cycles in air. The calculated temperature coefficient of resistivity (TCR) values vary between 1.4 and 5.5 × 10 −4 K −1 . Nano-sculptured spiral films exhibit consistently higher resistivity ( ρ  = 1.5 × 10 −6 Ω m) and TCR values (2.9 × 10 −4 K −1 ) than the inclined one with the same Ag content ( ρ  = 1.2 × 10 −6 Ω m and TCR = 2.0 × 10 −4 K −1 ). No significant changes are observed in the zigzag films concerning these properties. The effective anisotropy A eff at 473 K changes from 1.3 to 1.7 for the inclined films. Spiral films exhibit an almost completely isotropic behavior with A eff  = 1.1. Ag-rich TiAg core + shell Janus-like columns were obtained with increasing Ag concentrations.